The development of an interactive multimedia software program in library and information science - Cabbab, Johann Frederick A.; Pascua-Cruz, Ma. Divina A.; Soria, Robinson C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
A total of 78 (22 percent) students of the University of the Philippines Institute of Library Science of the total student population of 353 were chosen as respondents for this study to test the interactive multimedia software program developed based on the introductory courses in librarianship. Content data were collected, the program was designed and it was then developed using Object Pascal and HTML 3.3. The software used were Delphi 3 and Microsoft Frontpage Express.
The most common multimedia the respondents were exposed to were assorted CD encyclpedias. Of the 78 respondents, 77(98.718 percent) said 'yes' when asked if there was a need for a program such as this.
The interactive multimedia software program in library and information science holds much promise with the possibility of acceptance and use among the students of the University of the Philippines Institute of Library Science. Further testing for the software developed is recommended to allow it to evolve. Distribution of the software to other institutions offering Library and Information Science (LIS) would help education in LIS. The software may also be modified to develop modules other than introduction to libraries and librarianship. The software used in this study has capabilities for developing online and stand-alone databases. Developing databases from the programming level might be an option rather than studying how to customize existing database software. In this regard, it is also helpful if those taking LIS courses to be exposed to programming languages and higher math subjects.
Computer print out.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Interactive multimedia; Computer-assisted instruction -- Authoring programs